Heteromeric connexons in lens gap junction channels. - Jiang, J X (1996)
Gap junction channels are formed by paired oligomeric membrane hemichannels called connexons, which are composed of proteins of the connexin family. Experiments with transfected cell lines and paired Xenopus oocytes have demonstrated that heterotypic intercellular channels which are formed by two connexons, each composed of a different connexin, can selectively occur. Studies by Stauffer [Stauffer, K. A. (1995) J. Biol. Chem. 270, 6768-6772] have shown that recombinant Cx26 and Cx32 coinfected into insect cells may form heteromeric connexons. By solubilizing and subfractionating individual connexons from ovine lenses, we show by immunoprecipitation that connexons can contain two different connexins forming heteromeric assemblies in vivo.